Peningkatan Perdagangan Anak di Makassar: Sebuah Analisis Kriminologi - Nasrullah Nasrullah (SIGn Jurnal Hukum, 2023)
This research analyzes the factors contributing to escalating child trafficking activities in Makassar. This research uses an empirical legal research method with a criminology-based approach. All collected data is then qualitatively analyzed to describe the problem and answer the research objectives. The results show that the incidence of child trafficking in Makassar has escalated due to the complexity of multiple factors, including economic, community, education, social, gender inequality, technology, and law enforcement. Therefore, several recommendations can be proposed to the relevant stakeholders. First, the Makassar Municipal should consider implementing economic stabilization programs centered on protecting vulnerable children and families. Second, the development and enhancement of education quality should be prioritized, aiming to augment access to knowledge and awareness about children’s rights. Additionally, efforts to reduce poverty and promote gender equality must be intensified to prevent the exploitation of women and children. Third, the government and tech regulators must devise and implement policies to curb the misuse of social media in the context of child trafficking. Lastly, there must be an enhancement in law enforcement involving the optimization of the PPA Unit in its investigative role. Concurrently, inclusive and comprehensive legal reforms should be pursued to fortify the child protection system and mitigate the multifaceted factors exacerbating child trafficking in Makassar.